LANGUAGE, CULTURE AND IDENTITY: THE PORTUGUESE LANGUAGE AS A SYMBOLIC IDENTIFICATION SPACE ON DOCUMENTARY: LANGUAGE – LIVES IN PORTUGUESE - Santana, Joelton Duarte de (Linha D’Água, 2012)
Language as a social element is constitutive to every human being. Language gives each person, as well as to his or her own linguistic community, an individual and peculiar way to figure out the world and its surroundings. Language is influenced by several processes, including sociocultural and historical ones. If we say that each language may allow its speaker to do a very own world reading, a question about its language behavior in other continents arises. This way we were able to understand how sociocultural influences could improve the whole cultural identity construction process. Both defining linguistic communities and specifying social groups, language becomes a symbolic space of identification. The movie – Language- lives In Portuguese reunites Portuguese speakers reports around the world aiming to illustrate Portuguese language as a nations identity construction, autoafirmation and legitimation factor through social, cultural and historic processes. This study is based on the belief in such a kind of dialogism between Language and Culture. The sociolinguistic studies nowadays do not intend, as they used to, understanding or describing structural language aspects and very individuals ones, but especially to reflect upon relations among subject, language, identity, culture and history.